The Yemeni manuscript tradition - Hollenberg, David; Rauch, Christoph; Schmidtke, Sabine (Islamic manuscripts and books., 2015)
The Yemeni Manuscript Tradition contributes to the study of the manuscript codex and its role in scholastic culture in Yemen. Ranging in period from Islam¿́¿s first century to the modern period, all the articles in this volume emerge from the close scrutiny of the manuscripts of Yemen. As a group, these studies demonstrate the range and richness of scholarly methods closely tied to the material text, and the importance of cross-pollination in the fields of codicology, textual criticism, and social and intellectual history. Contributors are: Hassan Ansari, Menashe Anzi, Asma Hilali, Kerstin Hu¿nefeld, Wilferd Madelung, Arianna D¿́¿Ottone, Christoph Rauch, Anne Regourd, Sabine Schmidtke, Gregor Schwarb and Jan Thiele.